2022
DOI: 10.3390/curroncol29110689
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Cancer and Onset of Anxiety and Depression: A Systematic Review and Meta-Analysis

Abstract: Research suggests that colorectal cancer (CRC) is associated with mental health disorders, primarily anxiety and depression. To synthesize this evidence, we conducted a systematic review and meta-analysis of studies evaluating the onset of anxiety and depression among patients with CRC. We searched EMBASE and Medline from inception to June 2022. We included original, peer-reviewed studies that: used an epidemiologic design; included patients with CRC and a comparator group of individuals without cancer; and ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…Patients with cancer often need a multifaceted approach to address their myriad of supportive care concerns, including co-existing mental health needs [ 78 , 79 , 80 ]. For example, in patients with gastrointestinal cancers, the prevalence of depression and anxiety remains high, even after receiving cancer treatment [ 79 , 80 ]. Thus, innovation is necessary, especially in the mental health domain, to address these complex needs of patients with cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Patients with cancer often need a multifaceted approach to address their myriad of supportive care concerns, including co-existing mental health needs [ 78 , 79 , 80 ]. For example, in patients with gastrointestinal cancers, the prevalence of depression and anxiety remains high, even after receiving cancer treatment [ 79 , 80 ]. Thus, innovation is necessary, especially in the mental health domain, to address these complex needs of patients with cancer.…”
Section: Resultsmentioning
confidence: 99%
“…In previous literature, anxiety in cancer patients was positively associated with female sex, younger age, lower educational level, CRF, depression, more comorbidities, more advanced cancer stage, those who received cancer treatment (chemotherapy, radiotherapy, surgery), and those with a previous history of mental health problems [ 9 , 13 , 54 ]. By contrast, we found that a higher educational level was positively correlated with anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have confirmed that anxiety and depression are related to cancer mortality; however, to the best of our knowledge, no study has analyzed their relationship with all-cause mortality in patients with CRC [ 25 ]. Thus, we performed a meta-analysis to investigate the association of anxiety and depression with CRC along with their predictive factors, but we did not compile or analyze data on mortality [ 26 ]. Our meta-analysis is the first study to investigate the predictive value of depression and anxiety on CRC-related mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In 2019, Peng et al [ 8 ] published a literature review of 15 studies and reported that the prevalence rates of anxiety and depression in patients diagnosed with CRC were 1.0–47.2% and 1.6–57%, respectively. Studies have also shown that patients with CRC have a 51% increased risk of depression after diagnosis (pooled hazard ratio (HR), 1.51; 95% confidence interval (CI), 1.10–2.09) but have no association with anxiety (pooled HR, 1.43; 95% CI, 0.79–2.57) [ 9 ]. In addition, in 2021, a cohort study in Denmark reported that patients with CRC had a significantly higher risk of depression than cancer-free individuals, even after participating in the study for 5 years (HR, 2.65; 95% CI, 1.61–4.36) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%